The hippocampus and the flexible use and processing of language - Duff, Melissa C.; Brown-Schmidt, Sarah (Frontiers in Human Neuroscience, 2012)
Fundamental to all human languages is an unlimited expressive capacity and creative flexibility that allow speakers to rapidly generate novel and complex utterances. In turn, listeners interpret language “on-line”, incrementally integrating multiple sources of information as words unfold over time. A challenge for theories of language processing has been to understand how speakers and listeners generate, gather, integrate, and maintain representations in service of language processing. We propose that many of the processes by which we use language place high demands on and receive contributions from the hippocampal declarative memory system. The hippocampal declarative memory system is long known to support relational binding and representational flexibility. Recent findings demonstrate that these same functions are engaged during the real-time processes that support behavior in-the-moment. Such findings point to the hippocampus as a potentially key contributor to cognitive functions that require on-line integration of multiple sources of information, such as on-line language processing. Evidence supporting this view comes from findings that individuals with hippocampal amnesia show deficits in the use of language flexibly and on-line. We conclude that the relational binding and representational flexibility afforded by the hippocampal declarative memory system positions the hippocampus as a key contributor to language use and processing.